Blended Media Sinkronus dan Asinkronus untuk Meningkatkan Hasil Belajar Siswa di Sekolah Dasar - Ripto Saputri, Tera Noviantiningtyas; Permatasari, Cecilia; Mukmin, Bagus Amirul (Jurnal PGSD, 2021)
The Covid-19 pandemic has had a significant impact on all sectors, one of which is the education sector, namely elementary schools. The impact of the pandemic has made student learning outcomes decline because many teachers only use WhatsApp as a online learning medium. For this reason, there must be different learning innovations during the pandemic to be able to improve student learning outcomes. This innovation can be in the form of using synchronous Blended Media and Asynchronous Media on the theme of the area where I live in class IV Mojoroto 4, Kediri City. This research is a classroom action research with 4 stages starting from planning, implementing, observing, and reflecting. This research instrument uses a test sheet given to students. The results in this study there was a significant increase in student learning outcomes in cycle 3, marked by 86% of students scoring above the KKM and 14% below the KKM. Therefore, it can be concluded that there is an increase in student learning outcomes towards the use of synchronous and asynchronous blended media.Abstractadalahringkasan isiartikelyangmemuatpoin-poin penting setiapkomponenartikel.